Trends and Advances in Veterinary Genetics - Muhammad Abubakar (IntechOpen, 2017)
It is very important to understand the recent advances and basic concepts of veterinary genetics to explore the possibilities for control of diseases in animals. They are also significant for enhancing animal production and reproduction. Our book Trends and Advances in Veterinary Genetics provides a concise introduction and details to the aspects of genetics relevant to animal science and production. This is the first edition of the book so it covers the introductory level of topics which are ideal for veterinary students, classroom use, and practitioners who require more guidance with genetics. The book coverage includes the following main sections: Biotechnology and Reproductive Genetics, Advances in Embryonic Genetics, Conservation and Basic Genetics, and Veterinary Genetics and Future. Each book section comprises two chapters from renowned experts from the area and gives readers a unique opportunity to explore the topic.
English
Keywords: Veterinary Genetics; Veterinary Pathology; Veterinary Medicine and Science; Health Sciences